PUBLIC PROCUREMENT IN AFRICA AND THE INTEGRITY QUESTION: TOWARDS AN ETHICAL NARRATIVE - Tom Eneji Ogar; Ushie Abel Idagu (Social Sciences, Humanities and Education Journal (SHE Journal), 2020)
This work is an analysis of public procurement and the role integrity and ethics plays in enhancing effectiveness and efficiency of the procurement system. The paper situates that though public procurement is a worldwide exercise where government spends public funds for the procurement of goods works and services, for the good of the people, inefficiencies has trailed the procurement system in most developing countries of Africa. Some of these countries have taken some steps to reform the sector, but there are still noticeable challenges and obstacles to a full maximization of the goals of a good procurement system. One of the major challenges, identified has been that of a dearth of integrity and ethical consciousness on the part of procurement professionals and stakeholders alike. It is essential that public procurement professional and stake holders adhere to a well-defined and established code of ethics. Ethics are the principles which defines behaviours as right, good and appropriate. Employees in public service are expected to uphold certain core values and any attempt to pursue personal interest using conduct that are not consistent with the proper discharge of the employee’s duties is a breach of the public trust. In the public sector where procurement is funded by public expenditure, it is imperative that procurement operates with integrity, transparency and professionalism. In most African countries, Nigeria, Uganda, Tanzania to mention a few, the ethos of an efficient system devoid of unethical behaviours by professionals has been far from achieved. The procurement systems have therefore been plagued by integrity and ethical issues leading to unwholesome and undesirable situations. A review of related literatures to these topics was carried out with a view to carry out a contextual analysis in addressing the specific issues under study. This work is therefore significant as it tried to apply ethics to a fundamental aspect of governance which is the procurement of goods, services and works for the ultimate benefits of the populace.